Uji Daya Hambat Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa blimbi L.) Terhadap Pertumbuhan Staphylococcus epidermidis - Irma Zarwinda; Fauziah Fauziah; Shara Shevalinda; Dwi Putri Rejeki (Fakultas Teknik, 2021)
Startfruit (Averrhoa bilimbi L.) is one the kind of plant that is widely used as a traditional herbal medicineto overcome various diseases i.e. diabetes mellitus, cough, rheumatism, thrush, diabetes, toothache, acne, etc. The secondary metabolites of the starfruit leaves contain flavonoids and tannins, whereby these activecompounds can be used as an antibacterial. This study aimed to determine the inhibiting power of starfruit leaf ethanol extract against Staphylococcus epidermidis at concentrations of 25%, 50%, 75%, and 100%. The research was conducted at the AKAFARMA Laboratory and the Chemistry Laboratory , Faculty of Teacher Training and Education, Syiah Kuala University from June to July 2020. The research method was laboratory experimental using the disk diffusion method. The population of starfruit leaves was obtained from Lhokseumawe using a purposive sampling technique. Ethanol extract of starfruit leaves with concentrations of 25%, 50%, 75%, and 100%. The diameter of the inhibition zone of the ethanol extract from the starfruit leaves at concentrations of 100%, 75%, 50%, and 25% were 15 mm, 12 mm, 11 mm and 10 mm, respectively. It can be concluded that ethanol extract of starfruit leaves can inhibit the growth of Staphylococcus epidermidis with a maximum inhibitory concentration of 100%, which is classified as a strong category.